2014
DOI: 10.1002/lt.23813
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein 70 is required for optimal liver regeneration after partial hepatectomy in mice

Abstract: Liver regeneration is a complex process that restores functional tissue following resection or injury, and is accompanied by transient ATP depletion and metabolic stress in hepatic parenchymal cells. Heat shock protein-70 (Hsp70) functions as a chaperone during periods of cellular stress, and induces expression of several inflammatory cytokines identified as key players during early liver regeneration. We therefore hypothesized that Hsp70 would be required in the initiation of regeneration. Investigations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 23 publications
3
23
0
Order By: Relevance
“…A large body of evidence shows that the process of liver regeneration can benefit from hepatic preconditioning, which seems to involve a genetic responsetriggering of HSP expression [Pirkkala et al, 2001]. Recent evidence obtained in Hsp70 -/mice undergoing partial hepatectomy points to a fundamental role of HSP70 in the early stages of liver regeneration [Wolf et al, 2014], and supports earlier findings of low Hsp70 expression levels as a marker of acute rejection in human liver transplantation [Flohe et al, 1998].…”
Section: Discussionsupporting
confidence: 66%
“…A large body of evidence shows that the process of liver regeneration can benefit from hepatic preconditioning, which seems to involve a genetic responsetriggering of HSP expression [Pirkkala et al, 2001]. Recent evidence obtained in Hsp70 -/mice undergoing partial hepatectomy points to a fundamental role of HSP70 in the early stages of liver regeneration [Wolf et al, 2014], and supports earlier findings of low Hsp70 expression levels as a marker of acute rejection in human liver transplantation [Flohe et al, 1998].…”
Section: Discussionsupporting
confidence: 66%
“…It was found that extracellular Hsp70 can stimulate innate immune mechanisms by promoting the expression of tumor necrosis factor α and interleukin-6 and downstream nuclear factor kappa B signaling, all of which are biologically important components of early liver regeneration as reported by Joshua et al 29 .…”
Section: Fig 8: Minimum Energy Structure Of Compound E (Naa)mentioning
confidence: 80%
“…It also enhances liver regeneration through the reduced production of IFNγ and TNF‐α . In addition, dendritic cells as well as eosinophils are proved to regulate liver regeneration …”
Section: Discussionmentioning
confidence: 99%
“…(28) In addition, dendritic cells as well as eosinophils are proved to regulate liver regeneration. (29,30) However, little is known whether IL18 serves as a mediator of these immune cells in regulating liver regeneration and also in the corresponding signal pathway. It is reported that IL18 modulates liver inflammation by the recruitment of inflammatory cells, (12) and IL18 transgenic mice have a more prominent liver injury and hepatocyte apoptosis.…”
Section: Original Article | 415mentioning
confidence: 99%